Enhancing Students’ Academic Citation Literacy through Cybergogy-Based Supervision - Much Deiniatur; Dian Eka Priyantoro; Uswatun Hasanah; Suhono Suhono; Muhammad Khoirur Rofiki; Ridhwan Zaki (CV. Creative Tugu Pena, 2026)
The study aims to explore the supervision of research article writing for publication using reference manager software through the cybergogy model among undergraduate English Education students at one of the universities in Lampung. The research employed a narrative inquiry design involving 35 students and 3 lecturers of the Writing Research Article for Publication course. Data were collected through interviews, observations, document analysis, and students’ diary journals. The findings reveal that cybergogy-based supervision fostered students’ cognitive, emotional, and social engagement. Students were able to master technical skills in using a reference manager, generate consistent in-text citations and reference lists in APA style, and build academic collaboration during the course. Nevertheless, several challenges emerged, including technical difficulties, limitations in academic writing style, adaptation to journal templates, issues with the use of AI, and time management and writing consistency. Students addressed these challenges through self-practice, reflection using diary journals, and collaborative support from lecturers and peers. The study concludes that cybergogy-based supervision using reference management software is an effective strategy to enhance students’ ability to write publishable research articles.